Adhesion properties of polyacrylic block copolymer pressure‐sensitive adhesives and analysis by pulse NMR and AFM force curve. Issue 29 (29th March 2019) - Okada, Shun; Kashihara, Yusuke; Hirai, Tomoyasu; Fujii, Syuji; Nakamura, Yoshinobu; Urahama, Yoshiaki; Ito, Makiko; Liang, Xiaobin; Nakajima, Ken
ABSTRACT: The adhesion strength of a pressure‐sensitive adhesive (PSA) is influenced by two factors, the interfacial adhesion and the cohesive strength. A suitable method for the estimation of these two factors was investigated. Blends of triblock and diblock copolymers consisting of poly(methyl methacrylate) (hard) and poly( n ‐butyl acrylate) (soft) blocks (A) and blends of triblock copolymer and poly( n ‐butyl acrylate) oligomer (B), both with different blend ratios, were prepared as model PSAs. The peel strength decreased with an increase in the hard block content for B, whereas it was independent for A. The tack increased with a decrease in the hard block content for A, whereas it was independent for B. The influence of the hard block content on the peel strength and tack was thus different. The 1 H pulse nuclear magnetic resonance analysis and force curve analysis showed that the molecular mobility was higher for B than for A. The Young's modulus and adhesive energy calculated by the Johnson–Kendall–Roberts two‐point method using the atomic force microscopy (AFM) force curve qualitatively reflected the cohesive strength and the interfacial adhesion, respectively. The Young's modulus and adhesive energy are found to be useful parameters to investigate the adhesion mechanism. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47791. Abstract :